Serious games assisted by playware as a way to improve socio-emotional skills in children with autism spectrum disorder - Azevedo, José Pedro Coelho (2018)
This paper presents a project developed with the aim of promoting emotional skills in children with Autism Spectrum Disorders (ASD). The project involves a serious game and a playware object, which is a physical component that allows the user to interactively play the serious game. The playware object has six buttons, each one showing an emoji with a specific facial expression and communicates via Bluetooth with the serious game app installed in an Android device. The facial expressions used are: happiness, sadness, fear, anger, surprise and neutral/normal. They were applied to the three game activities (imitation, recognition and storytelling). The chain of tests started with an online questionnaire to validate the avatars created to represent the previously mentioned facial expressions in the game, which was followed by a usability test of the application (serious game and playware object) with six typically developing children. Finally, the three game activities were tested with six children with ASD in three/four sessions. Due to the small test group and reduced number of sessions, the primary objective was to assess if the target group accepted the application. In fact, it had a high level of approval regarding both the serious game and the playware object. had a high level of approval regarding both the serious game and the playware object.